Second Five Year Plan Government of Saurashtra - Planning Commission (Planning Commission, 1956)
The State of Saurashtra was formed as a result of the merger of 222 states and estates in the peninsula of Kathiawar. These states and estates were cut up into 800 and odd administrative units. It needs little elaboration to bring out the fact that the existence of these small units was a hindrance to progress in Kathiawar.
Government of Saurashtra, Directorate of Statistics and Planning